Bilateral relations between Colombia and Switzerland: Effects on the colombian dairy sector in the period 1992-2007 (2020)
From 1992 to 2007, the Colombian dairy sector was influenced in many different ways by the big Swiss dairy enterprises that have worked in the country since the origin of the Treaty of Friendship, Commerce and Establishment in the year 1908. In this review the commercial effects generated on the national dairy sector by the Swiss enterprises and the dilemma presented between the Colombian dairy sector and the Swiss dairy enterprises are analyzed.